Analysis of Influencing Factors of Organizational Health Literacy in Healthcare Institutions in Beijing, China: A Cross-Sectional Study - Qin T; Guo J; Yang Y; Gu M; Wang Y; Li X (Dove Medical Press, 2024)
Tingting Qin,1,* Junjun Guo,2,* Yutong Yang,2 Mingyu Gu,2 Yao Wang,2 Xingming Li2 1Department of Science and Technology, Beijing Shijitan Hospital, Capital Medical University, Beijing, People's Republic of China; 2School of Public Health, Capital Medical University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xingming Li, School of Public Health, Capital Medical University, No. 10 Xitoutiao, Youanmenwai, Fengtai District, Beijing, 100069, Email xingmingli@ccmu.edu.cnObjective: This study aimed to evaluate the organizational health literacy of healthcare institutions in Beijing and to analyse its influencing factors to provide suggestions for the construction of health-promoting medical institutions.Methods: This study used multi-stage cluster sampling and conducted an online survey of medical staff in the sampled healthcare institutions in Beijing from May to July 2023. The Chinese version of the Health Literate Health Care Organization 10-item Questionnaire (HLHO-10-C) was used to assess the organizational health literacy of healthcare institutions. Univariate analysis and generalized linear models (GLM) were used to analyze the influencing factors.Results: Finally, 2527 participants were included. The majority of participants were female (87.6%). More than half of the participants indicated that they had engaged in outpatient or inpatient health education work. The respondents' score for HLHO-10-C was 6.170± 1.056. The score of the respondents from tertiary hospitals (6.003± 1.167) was slightly lower than those from secondary hospitals (6.328± 0.747) and primary healthcare centers (6.418± 0.864). All healthcare institutions scored relatively high on institutional environmental construction support (6.284± 1.034). The results of the GLM showed that educational level, healthcare institution level, and engagement in health education work were factors influencing HLHO-10-C (P< 0.05).Conclusion: Overall, the organizational health literacy of healthcare institutions in Beijing was relatively good. However, there is room for improvement in tertiary hospitals. In the future, to promote the construction of health-literate hospitals, targeted measures should be taken to encourage healthcare workers to engage in health education.Keywords: health literate health care organization, Health literate, health education, hospitals